Interstrand cross-linking by Adriamycin in nuclear and mitochondrial DNA of MCF-7 cells - Cullinane, Carleen (Oxford University Press, 2000)
Activation of Adriamycin by formaldehyde leads to the formation of drug–DNA adducts in vitro and these adducts stabilise the DNA to such a degree that they function as virtual interstrand cross-links. The formation of these virtual interstrand cross-links by Adriamycin was investigated in MCF-7 cells using a gene-specific interstrand cross-linking assay. Cross-linking was measured in both the nuclear-encoded DHFR gene and in mitochondrial DNA (mtDNA). Cross-link formation increased linearly with Adriamycin concentration following a 4 h exposure to the drug. The rate of formation of Adriamycin cross-links in each of the genomes was similar, reaching maximal levels of 0.55 and 0.4 cross-links/10 kb in the DHFR gene and mtDNA respectively, following exposure to 20 µM Adriamycin for 8 h. The interstrand cross-link was short lived in both DNA compartments, with a half-life of 4.5 and 3.3 h in the DHFR gene and mtDNA respectively. The kinetics of total Adriamycin adduct formation, detected using [(14)C]Adriamycin, was similar to that of cross-link formation. Maximal adduct levels (30 lesions/10 kb) were observed following incubation at 20 µM drug for 8 h. The formation of such high levels of adducts and cross-links could therefore be expected to contribute to the mechanism of action of Adriamycin.